SOSIALISASI DAN BANTUAN HUKUM GRATIS BAGI UMKM KOTA BAUBAU DALAM ASPEK LEGALITAS USAHA - Abdullah, La Ode Dedi; Pratiwi, Endang Tri; Abdullah, Rudi; Agustina, Wa Ode (Jurnal Pengabdian Masyarakat Berkarya, 2024)
Title of article is Legal Awareness and Free Legal Assistance for MSMEs in Baubau City Regarding Business Legality Aspects. This program aims to improve MSME actors' understanding of business legality importance in Baubau City through legal awareness campaigns and free legal assistance. Most MSMEs in Baubau lack complete business permits due to limited understanding of procedures and benefits of business formalization. Implementation methods include: (1) legal counseling on business permits (NIB, SIUP, Halal Certificate), (2) assistance in document processing, and (3) free legal consultations. The program collaborates with Baubau City's Cooperative and MSME Office and local BPKM Office. Results show 75% increase in participants' understanding of legal business requirements and completion of 50 MSME legal documents during the program. This initiative not only helps fulfill legal obligations but also enhances MSMEs' competitiveness in the formal market.